Study of Surge Phenomena in a Hydropower Plant: A Numerical Approach - Timilsina, Prabin; Chaulagain, Nabin Raj; Bijukchhe, Pawan Lal; Chitrakar, Sailesh (Kathmandu University Journal of Science, Engineering and Technology, 2021)
Sudden closure and opening of valves might cause unwanted water hammering effects in hydropower plants. In many cases, surge shafts are used as pressure neutralizers to dampen out the generated pressure pulsations. This study focuses on analyzing the surge phenomena and effects of using simple surge and restricted orifice surge on the flow behavior during the closing and opening of turbine inlet valves. A case of a Nepalese hydropower plant was taken and calculations were done over a simplified water transportation system of the plant. Analytical result was compared with the result obtained from an open-source CFD toolbox, OpenFOAM. A 3D fluid domain was made in SolidWorks and the mesh was created using snappyHexMesh utility of OpenFOAM. This study uses a multiphase solver called interFoam with the implementation of κ-ω SST turbulence model. The analytical result for maximum increase in water level in the surge shaft was calculated as 18.68 meters assuming a case of U-tube oscillation. The calculations neglected the presence of penstock pipes and assumed instantaneous closure thus giving a maximum value for upsurge height. Similar physical condition was recreated in OpenFOAM but with the presence of penstock, and a change in surge height with respect to time was analyzed. The obtained CFD result showed the average water level height in surge shaft to be 11.23 meters, which is less than the analytical result as expected. Then, the time of closure and time of opening were increased to 6 seconds and 30 seconds respectively and the effect of surge with and without orifice were visualized with respect to mass oscillations, pressure inside penstock and velocity of water in headrace tunnel. The numerical techniques used in this study can be applicable to other hydropower plants, which could provide a basis for the verification of the analytical designs.